Peran dan dampak Teknologi digiTal pada Disain InterioR FSR ISI Yogyakarta - Martino Dwi Nugroho (Ars: Jurnal Seni Rupa dan Desain, 2011)
The Role and Impact of Technology on the Interior Design Study Program of ISI Yogyakarta. Digital technology grows rapidly and covers all fields in life. The design education conducted by the Visual Art Faculty of ISI Yogyakarta manages to cope with the technology development. This progress does not only set changes in technical aspects such as equipment and material, but also includes a wider range of issues correlated with the designing concept, the users’ responses and the designers’ attitude in the process of creating their works of art. The development of interior design in Indonesia can be tracked from four periods of development: the colonization era, the guided democracy era, the new order era, and the 21st century design era. The Interior Design Study Program, as other study programs existing in the Faculty of Visual Art of ISI Yogyakarta is branded for excellent manual skills. The application of digital technology in its teaching-learning process should ponder many aspects: hardware, software, maintenance, and human capital. Thoughtful researches are required to be able to follow the world development and show the uniqueness of this art education institution